Strategi Guru Pendidikan Agama Islam Sebagai Konselor Islami Dalam Mengatasi Kecanduan Game Online Siswa - Azman Azman; Ayu Irawan (EL-EMIR Institute, 2026)
This study aims to demonstrate the strategies of Islamic Religious Education (PAI) teachers as natural counselors in overcoming online gaming addiction in students. Online gaming addiction in students is a problem affecting their academic, social, emotional, and spiritual development. Therefore, the role of PAI teachers is not only as educators but also as counselors who provide guidance and support based on Islamic values. This study used a qualitative approach with library research methods. Data were obtained from various sources such as books, scientific journals, articles, and documents relevant to the research topic. The results indicate that PAI teachers' strategies as Islamic counselors can be implemented through providing religious guidance, strengthening moral and spiritual values, individual and group counseling, fostering worship habits, monitoring technology use, and collaborating with parents and schools. An Islamic counseling approach based on the Qur'an and Hadith has been proven to help students improve self-control, manage their time effectively, and reduce dependence on online gaming. Thus, the Islamic Religious Education teacher's strategy as an Islamic counselor plays a crucial role in shaping students' character to be more disciplined, responsible, and balanced in their use of technology.